Systemic Supplementation of Collagen VI by Neonatal Transplantation of iPSC-Derived MSCs Improves Histological Phenotype and Function of Col6-Deficient Model Mice - Harada, Aya; Goto, Megumi; Kato, Atsuya; Takenaka-Ninagawa, Nana; Tanaka, Akito; Noguchi, Satoru; Ikeya, Makoto; Sakurai, Hidetoshi (Frontiers in Cell and Developmental Biology, 2021)
Collagen VI is distributed in the interstitium and is secreted mainly by mesenchymal stromal cells (MSCs) in skeletal muscle. Mutations in COL6A1-3 genes cause the spectrum of COL6-related myopathies. In this study, we performed a systemic transplantation study of human induced pluripotent stem cell (iPSC)-derived MSCs (iMSCs) into neonatal immunodeficient COL6-related myopathy model (Col6a1KO/NSG) mice to validate the therapeutic potential. Engraftment of the donor cells and the resulting rescued collagen VI were observed at the quadriceps and diaphragm after intraperitoneal iMSC transplantation. Transplanted mice showed improvement in pathophysiological characteristics compared with untreated Col6a1KO/NSG mice. In detail, higher muscle regeneration in the transplanted mice resulted in increased muscle weight and enlarged myofibers. 8-week-old mice showed increased muscle force and performed better in the grip and rotarod tests. Overall, these findings support the concept that systemic iMSC transplantation can be a therapeutic option for COL6-related myopathies.